2019
DOI: 10.5194/acp-2019-398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A review of experimental techniques for aerosol hygroscopicity studies

Abstract: <p><strong>Abstract.</strong> Hygroscopicity is one of the most important physicochemical properties of aerosol particles, and also plays indispensable roles in many other scientific and technical fields. A myriad of experimental techniques, which differ in principles, configurations and cost, are available for investigating aerosol hygroscopicity under subsaturated conditions (i.e., relative humidity below 100 %). A comprehensive review of these techniqu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 295 publications
(567 reference statements)
0
13
1
Order By: Relevance
“…A wide range of experimental techniques are available to study the hygroscopic properties of particles in sub-saturated (< 100 % RH) conditions, including humidity-tandem differential mobility analyzers (H-TDMAs), various optical extinction and scattering methods, physisorption analyzers, quartz crystal microbalances and various microscopic and spectroscopic methods (Kreidenweis and Asa-Awuku, 2014;Tang et al, 2019). A drawback of many of the otherwise highly valuable traditional aerosol techniques, such as the H-TDMA or optical methods, is that they are based on detection of growth in mass or volume.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of experimental techniques are available to study the hygroscopic properties of particles in sub-saturated (< 100 % RH) conditions, including humidity-tandem differential mobility analyzers (H-TDMAs), various optical extinction and scattering methods, physisorption analyzers, quartz crystal microbalances and various microscopic and spectroscopic methods (Kreidenweis and Asa-Awuku, 2014;Tang et al, 2019). A drawback of many of the otherwise highly valuable traditional aerosol techniques, such as the H-TDMA or optical methods, is that they are based on detection of growth in mass or volume.…”
Section: Introductionmentioning
confidence: 99%
“…A number of spectroscopic techniques have been applied to systems of environmental and atmospheric relevance (see, e.g., the reviews of Ault and Axson, 2016;Tang et al, 2019). Surface-sensitive techniques such as X-ray photoelectron spectroscopy (XPS) provide molecular-level information on the chemical composition and properties of surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While hygroscopicity and CCN activity are closely related, studies have shown that measurements of hygroscopicity at subsaturated RH can deviate 45 from estimates of hygroscopicity derived from CCN activity measurements, attributable to solubility and surface tension effects (Petters and Kreidenweis, 2013Ruehl et al, 2010Ruehl et al, , 2016. Deriving a complete understanding of the CCN activity and physical properties of aerosol particles across the full range of RH requires a careful approach utilizing both experimental methods and models (Tang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The authors may consider discussing how advances in orthogonal fields may be of future importance to atmospheric measurements. For example, although not currently relevant to aerosol, the production of highly sensitive humidity sensors should be considered (e.g., Liang et al, 2018 ). The Dash-P and HFIMS, use faster sizing instrumentation however faster RH technology may also advance studies.…”
mentioning
confidence: 99%